Smart Education and e-Learning 2017 (Smart Innovation, Systems and Technologies,, 2018)
This book gathers the contributions presented at the 4th International KES Conference on Smart Education and Smart e-Learning (KES-SEEL-17), which took place in Vilamoura, Algarve, Portugal, June 21-23, 2017. Smart education and smart e-Learning are emerging and rapidly growing areas. They represent the innovative integration of smart systems, technologies and objects, smart environments, smart pedagogy, smart learning and academic analytics, various branches of computer science and computer engineering, and state-of-the-art smart educational software and/or hardware systems. It contains a total of 48 peer-reviewed book chapters that are grouped into several parts: Part 1 - Smart Pedagogy, Part 2 - Smart e-Learning, Part 3 - Systems and Technologies for Smart Education, Part 4 - Smart Teaching, and Part 5 - Smart Education: National Initiatives and Approaches. The book offers a valuable source of research data, information on best practices, and case studies for educators, researchers, Ph.D. students, administrators, and practitioners-and all those who are interested in innovative areas of smart education and smart e-Learning.